Factors Influencing Interest in Using Financial Technology QRIS Among Accounting Lecturers in Bandar Lampung-Indonesia - Septiani, Kamelia; Yuniarti, Evi; Rusmianto; Wijaya, Lihan Rini Puspo; Kurniawan, Umarudin (Ilomata International Journal of Tax and Accounting, 2024)
The use of QRIS as a digital payment method is increasing in Indonesia. QRIS provides convenience in payments so that the transaction process becomes more effective and efficient. This study aims to determine the influence of promotional attractiveness, perception of ease of use, and perception of use risk on interest in using Financial Technology QRIS in Accounting Lecturers in Bandar Lampung City. The population of this study is Accounting Lecturers of PTN and PTS in Bandar Lampung City. Data collection was carried out by distributing questionnaires to 61 respondents. Data analysis was carried out using SEM models and the help of Smart PLS software. From the hypothesis test, it was found that the attractiveness of promotion had no effect on the interest in using QRIS financial technology and the perception of ease of use had no effect on the interest in using QRIS financial technology. Meanwhile, the perception of risk of use has no effect on interest in using QRIS financial technology.